2018
DOI: 10.7759/cureus.3664
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation in Patients with Chronic Lung Impairment from Pulmonary Tuberculosis

Abstract: SettingOur study was conducted at a tertiary care center for respiratory illnesses (Viswanathan Chest Hospital, Vallabhbhai Patel Chest Institute (VPCI), University of Delhi, Delhi, India). Patients were enrolled in the study from the outpatient clinic.ObjectiveTo assess the effects of pulmonary rehabilitation (PR) in patients with chronic lung impairment from previously treated tuberculosis (CLIPTB), on exercise capacity (six-minute walk distance), pulmonary function tests, quality of life and markers of syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 23 publications
1
27
0
5
Order By: Relevance
“…Before initiating a specific rehabilitation programme, patients should undergo a complete lung functional assessment, including spirometry and exercise capacity testing to enable an appropriate exercise training regime. Exercise capacity is usually based on cardiopulmonary exercise testing or walking tests (6MWT, incremental shuttle walking test (ISWT)) in order to set physical training sessions that exceed the physical loads of daily life activities [45,[51][52][53][54][55][56][57][58]. Some studies documented the positive role of aerobic training on symptoms, anxiety, depression, and QoL [45,[51][52][53][54][55][56][57][58].…”
Section: Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Before initiating a specific rehabilitation programme, patients should undergo a complete lung functional assessment, including spirometry and exercise capacity testing to enable an appropriate exercise training regime. Exercise capacity is usually based on cardiopulmonary exercise testing or walking tests (6MWT, incremental shuttle walking test (ISWT)) in order to set physical training sessions that exceed the physical loads of daily life activities [45,[51][52][53][54][55][56][57][58]. Some studies documented the positive role of aerobic training on symptoms, anxiety, depression, and QoL [45,[51][52][53][54][55][56][57][58].…”
Section: Exercise Trainingmentioning
confidence: 99%
“…In the vast majority of the studies, the spirometry parameters, oxygen saturation, and exercise capacity tests (6MWT or ISWT, range 35-110 m) improved significantly. When QoL tests were performed, they also improved significantly [45,[51][52][53][54][55][56][57][58]. Unfortunately the different studies reported different parameters, making a meta-analytic evaluation difficult.…”
Section: Effectiveness Of Pulmonary Rehabilitation In Tbmentioning
confidence: 99%
“…The exercise programme consisted of daily walking in the hospital corridor, and the results were positive: increase of maximum oxygen uptake (from 13. (29). By resuming, for the evaluation of PR programmes results in patients with TB, the parameters used were as follows:…”
Section: Exercise Trainingmentioning
confidence: 99%
“…-exercise tolerance with 6MWT (22,23,29), ISWT 7and CPET (28). -QOL with SGRQ (St George Respiratory Questionnaire) (22,28), CCQ (Clinical COPD Questionnaire) (7), WHOQOL-100 (quality of life of the World Health Organization) (5), CRQ (29).…”
Section: Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation